The Power of Affect: Teacher Activism as Resistance to Neoliberalism in Saskatchewan (Alberta Journal of Educational Research, 2022)
With prevailing global neoliberal ideology, teachers and teacher unions must respond to market-driven governmental policies intended to undermine public education. In Saskatchewan, Canada, teacher activists feel compelled to both counter neoliberal discourses and proactively advocate for equitable, high-quality public education. To explore acts of resistance, semi-structured interviews with four teacher activists were employed to understand how teachers enact advocacy within their union and through grassroots activism. Harding et al.’s (2018) framework of alliances, assemblages, and affects informed data analysis, which included the creation of narrative vignettes characterizing teacher voice. This paper specifically discusses findings which suggest that affect, or how emotions do things, presented teachers with new potentialities for shaping educational policy.Keywords: narrative inquiry, teacher unions, grassroots teacher activism, neoliberalism, poststructuralism, affectFace à l'idéologie néolibérale mondiale dominante, les enseignants et les syndicats d'enseignants doivent répondre aux politiques gouvernementales axées sur le marché et destinées à saper l'éducation publique. En Saskatchewan, au Canada, les enseignants militants se sentent obligés de contrer les discours néolibéraux et de défendre de manière proactive une éducation publique équitable et de qualité. Des entretiens semi-structurés avec quatre enseignants militants ont été utilisés pour explorer les actes de résistance et comprendre comment les enseignants défendent leurs intérêts au sein de leur syndicat et par le biais du militantisme de base. Le cadre d'alliances, d'agencements et d'affects de Harding et al. (2018) a guidé l'analyse des données, qui comprenait la création de vignettes narratives caractérisant la voix des enseignants. Cet article traite spécifiquement des résultats qui suggèrent que l'affect, ou la façon dont les émotions font les choses, a présenté aux enseignants de nouvelles potentialités pour façonner la politique éducative.Mots clés : enquête narrative, syndicats d'enseignants, activisme des enseignants de la base, néolibéralisme, poststructuralisme, affect